2012
DOI: 10.1186/1742-4682-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bizhongxiao decoction and its dismantled formulae on IL-1 and TNF levels in collagen-induced arthritis in rat synovial joints

Abstract: BackgroundRheumatoid arthritis (RA), a chronic autoimmune disease, affects sufferers in many different ways. Treatment of this chronic condition is particularly challenging. Traditional Chinese Medicine (TCM) provides alternatives. Bizhongxiao decoction (BZX) is a TCM complex, which has been used clinically for many years to treat RA. The purpose of this study is to compare the effects of BZX decoction and its dismantled formulae on IL-1 and TNF-1 levels in rats with RA, and to elucidate its mechanism of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Rats were divided into 2 groups, that is, the OD group ( n = 5) and the control group ( n = 5). First, we calculated the standard human daily herbal dose and converted it to a rat daily herbal dose according to the body surface area of an individual weighing 70 kg [ 16 ]; the daily dose per rat was thus 2.7 mg/g (crude drug/weight). We administered the OD decoction orally at the calculated dose to the OD group and administered the same volume of purified water to the control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were divided into 2 groups, that is, the OD group ( n = 5) and the control group ( n = 5). First, we calculated the standard human daily herbal dose and converted it to a rat daily herbal dose according to the body surface area of an individual weighing 70 kg [ 16 ]; the daily dose per rat was thus 2.7 mg/g (crude drug/weight). We administered the OD decoction orally at the calculated dose to the OD group and administered the same volume of purified water to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…After 14 days, we randomly divided the replication group into an OD group, a p-CA group, and a model group. Based on the results of the previous chromatographic analysis, we calculated the p-CA content in OD and converted this to a rat dose [ 16 ]. Based on the normal human daily herbal dose, we calculated the daily dose of p-CA for a rat, which was 13.8 μ g/g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tocotrienol increased AMPK phosphorylation. In previous studies, g-tocotrienol demonstrated an inhibitory effect on the NF-κB activation pathway [24][25][26][27]. Moreover, Wu et al [28] identified that a tocotrienol-rich fraction was capable of inhibiting proinflammatory cytokine production in human monocytes.…”
Section: Discussionmentioning
confidence: 97%
“…The serum was used in an enzyme linked immunosorbent assay (ELISA) kit (Wuhan Huamei Biotech Co., LTD) to detect the levels of IL-1β and TNF-α. 23 …”
Section: Methodsmentioning
confidence: 99%